Issuing the Licenses the Serbian System of Shared Cataloguing COBISS.SR - Dakić, Nataša (Infotheca - Journal for Digital Humanities; Vol 8 No 1/2 (2007): Infotheca - Journal of Informatics and Librarianship, 2024)
From the beginning of the shared cataloguing system in Yugoslavia, from 1988 till its disintegration in 1992, in order to work in shared cataloguing system, librarians had to go through instructions which consisted of 5 days course. In Slovenia, conditions for issuing licenses for shared cataloguing were regulated in 2001 through the Law on librarianship, and in 2005 enlarged on the bases of the Rules on issuing permission for shared cataloguing. These Rules includes also the conditions for suspending the license. In Serbia, from the establishment of united national bibliographic-information system COBISS.SR in 2003, license for work in the shared catalogue is issued to a cataloguer who, after 5 day course, successfully creates 30 records in test base. In order to increase the quality of the shared base COBIB.SR it is necessary to establish the Rules for issuing the permisssion for shared cataloguing, by which conditions for issuing or suspending the license would be clearly defined, as well as the rights and obligations of the partners in shared cataloguing.